Ecto-5′-Nucleotidase (CD73) Deficiency in Mycobacterium tuberculosis-Infected Mice Enhances Neutrophil Recruitment - Petit-Jentreau, Laetitia (Infect Immun, 2015)
The immune system needs safeguards that prevent collateral tissue damage mediated by the immune system while enabling an effective response against a pathogen. The purinergic pathway is one such mechanism and finely modulates inflammation by sensing nucleotides in the environment. Extracellular ATP is considered to be a danger signal leading to a proinflammatory response, whereas adenosine is immunosuppressive. CD73, also called ecto-5′-nucleotidase, occupies a strategic position in this pathway, as it is the main enzyme responsible for the generation of adenosine from ATP. Here, we explore the role of CD73 during tuberculosis, a disease characterized by an immune response that is harmful to the host and unable to eradicate Mycobacterium tuberculosis. Using CD73 knockout (KO) mice, we found that CD73 regulates the response to M. tuberculosis infection in vitro and in vivo. Mycobacterium-infected murine macrophages derived from CD73 KO mice secrete more keratinocyte chemoattractant (KC), tumor necrosis factor alpha (TNF-α), and interleukin-6 (IL-6) and release less vascular endothelial growth factor (VEGF) upon ATP stimulation than do those derived from wild-type (WT) mice. In vivo, CD73 limits the early influx of neutrophils to the lungs without affecting bacterial growth and dissemination. Collectively, our results support the view that CD73 fine-tunes antimycobacterial immune responses.